The European aerospace R&D collaboration network - Daniel Guffarth; Michael J. Barber (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2013)
We describe the development of the European aerospace R&D collaboration network from 1987 to 2013 with the help of the publicly available raw data of the European Framework Programmes and the German Förderkatalog. In line with the sectoral innovation system approach, we describe the evolution of the aerospace R&D network on three levels. First, based on their thematic categories, all projects are inspected and the development of technology used over time is described. Second, the composition of the aerospace R&D network concerning organization type, project composition and the special role of SMEs is analyzed. Third, the geographical distribution is shown on the technological side as well as on the actor level. A more complete view of the European funding structure is achieved by replicating the procedure on the European level to the national level, in our case Germany.
urn:nbn:de:bsz:100-opus-9038
Keywords: 330